MELIHAT KEHIDUPAN MISKIN KOTA PERSPEKTIF TUKANG SAPU JALANAN - Sry Ayu Astuti Sitohang; Kuperju Syahputra (Kampus Akademik Publiser, 2024)
Abstract. This study aims to examine how the lives of street sweepers in the city can be improved and how they can gain better access to health services, education, and economic opportunities. This research aims to provide new insights into the lives of street sweepers in the city. By using the Theory of Social Poverty as a basis for understanding poverty as a social problem. This research uses secondary data and personal observations as a means of data collection, which will then be explained using a descriptive qualitative method. Poverty in urban Indonesia is still a serious issue, with the percentage of poor people reaching 7.29% in 2023. Street sweepers are included in the category of laborers with characteristics of manual work, low wages, and minimal social security. To survive, they are forced to live in slums, reduce social activities, and even borrow money with high interest rates. The government has made efforts to improve their welfare, but the implementation still faces challenges such as budget limitations and difficulties in reaching informal workers.